113P A phase I study of an anti-IDO1 inhibitor (LY3381916) as monotherapy and in combination with an anti-PD-L1 antibody (LY3300054) in patients with advanced cancer. (15th December 2019) - Kotecki, N; O'Neil, B; Jalal, S; Massard, C; Wallin, J; Szpurka, A; Wang, D; Galvao, V Regnier; Xia, M S; Crowe, K; Geeganage, S; Doman, T; et al.
Abstract: Background: JZCA is a phase Ia/Ib study with the primary objective to assess the safety and tolerability of LY3381916 as monotherapy (Part A) and in combination with LY3300054, an anti-PD-L1 antibody (Part B). In the doseescalation part, safety, efficacy, pharmacokinetics (PK), and pharmacodynamics (PD) of LY3381916 monotherapy (Part A) and in combination with LY3300054 (Part B) were investigated in patients (pts) with advanced solid tumors to determine the recommended phase II dose (RP2D). Methods: Pts with advanced/metastatic solid tumors received LY3381916 orally from 60mg-600mg once daily (QD), 240mg twice daily (BID) (Part A), or LY3381916 60mg-240mg QD in combination with LY3300054 700mg intravenously every 2 weeks (Part B). Results: LY3381916 was administered to 42 pts at the cut-off date of July 12, 2019. The most common treatmentrelated adverse events (AEs) were nausea and fatigue. Dose-limiting toxicities were observed in 3 pts (1 pt, Part A 240mg BID with Grade 3 [Gr] ALT/AST increase and systemic inflammatory response syndrome; 2 pts, Part B 240mg QD with Gr 3 fatigue and Gr 3 immunerelated hepatitis). The best objective response was SD, with 7 pts in monotherapy and 5 pts in combination dose escalation. LY3381916 clearance was 12 L/h; mean terminal half-life was ∼6h. Increases in drug exposure were proportional to dose with no apparent differences in PK between monotherapy and combination therapy. In monotherapy pts, PD data showed >90% IDO1 inhibition in ex-vivo whole blood and sustained reduction of plasma kynurenine (Kyn) at steady state for all doses. Sustained plasma Kyn reduction was observed in 76% of combination pts. Tumor tissue Kyn levels were decreased in > 60% of pts with treatment (67% mono; 64% combo). An increase in tumor CD8+ T cells (IHC and RNA-seq) was predominantly observed at the 240mg QD dose with LY3300054. RNA-seq expression was consistent with a dose-dependent increase in activated CD8 effector T cells (i.e., granzyme B, perforin) in the combination treatment. Conclusion: LY3381916 is safely administered as monotherapy and in combination with LY3300054. The 240mg dose QD is the RP2D for combination with PD-L1 in expansion cohorts. Clinical trial identification: NCT03343613. Editorial acknowledgement: Editorial assistance was provided by Gina Moore, Syneos Health. Legal entity responsible for the study: Eli Lilly and Company. Funding: Eli Lilly and Company. Disclosure: B. O'Neil: Shareholder / Stockholder / Stock options: Eli Lilly and Company; Full / Part-time employment: Eli Lilly and Company. S. Jalal: Research grant / Funding (institution): AstraZeneca; Research grant / Funding (institution): Tesaro; Research grant / Funding (institution): Astex. C. Massard: Honoraria (institution): Eli Lilly and Company. J. Wallin: Shareholder / Stockholder / Stock options: Eli Lilly and Company; Full / Part-time employment: Eli Lilly and Company. A. Szpurka: Shareholder / Stockholder / Stock options: Eli Lilly and Company; Full / Part-time employment: Eli Lilly and Company; Spouse / Financial dependant: Eli Lilly and Company. D. Wang: Full / Part-time employment: Eli Lilly and Company. V. Regnier Galvao: Shareholder / Stockholder / Stock options: Eli Lilly and Company; Full / Part-time employment: Eli Lilly and Company. M.S. Xia: Full / Part-time employment: Eli Lilly and Company. K. Crowe: Full / Part-time employment: Eli Lilly and Company. S. Geeganage: Shareholder / Stockholder / Stock options: Eli Lilly and Company; Full / Part-time employment: Eli Lilly and Company. T. Doman: Shareholder / Stockholder / Stock options: Eli Lilly and Company; Full / Part-time employment: Eli Lilly and Company; Spouse / Financial dependant: DWA Health Care Communications Group. L. Gandhi: Shareholder / Stockholder / Stock options: Eli Lilly and Company; Full / Part-time employment: Eli Lilly and Company. X. Xu: Shareholder / Stockholder / Stock options: Eli Lilly and Company; Full / Part-time employment: Eli Lilly and Company. J. Bendell: Research grant / Funding (institution): Genentech/Roche; Research grant / Funding (institution): Bristol-Myers Squibb; Advisory / Consultancy: Five Prime; Research grant / Funding (institution): Lilly; Advisory / Consultancy: Merck; Advisory / Consultancy: Medimmune; Advisory / Consultancy: Celgene; Research grant / Funding (institution): EMD Serono; Advisory / Consultancy, Research grant / Funding (institution): Talhho; Advisory / Consultancy: Marcogenics; Research grant / Funding (institution): GSK; Research grant / Funding (institution): Novartis; Research grant / Funding (institution): OncoMed; Research grant / Funding (institution): LEAP therapeutics; Research grant / Funding (institution): TG therapeutics; Research grant / Funding (institution): AstraZeneca; Advisory / Consultancy: BI; Advisory / Consultancy, Research grant / Funding (institution): Daiichi Sankyo; Research grant / Funding (institution): Bayer; Research grant / Funding (institution): Incyte. All other authors have declared no conflicts of interest.